Throughput Analysis for a High-Performance FPGA-Accelerated Real-Time Search Application. (19th January 2012) - Vanderbauwhede, Wim; Chalamalasetti, S. R.; Margala, M.
Abstract : We propose an FPGA design for the relevancy computation part of a high-throughput real-time search application. The application matches terms in a stream of documents against a static profile, held in off-chip memory. We present a mathematical analysis of the throughput of the application and apply it to the problem of scaling the Bloom filter used to discard nonmatches.